Assessing production potential and quality parameters of ELS cotton (Gossypium barbadense) genotypes - SANKARANARAYANAN, K; PRAKASH, A H; MANIVANNAN, A; SABESH, M (The Indian Journal of Agricultural Sciences, 2021)
There is a huge demand for ELS cotton (Gossypium barbadense L.) in India for its premium fibre properities, however, the area and production of ELS is very less.There is a considerable scope for extending the area of ELS under rainfed condition to increase the production. But the fibre quality got severely affected due to moisture stress in rainfed condition as the crop has long phase of growing period. Hence the experiment is conducted to ascertain the relationship between phenological periods with quality parameters to identify sensitive phenological periods for better crop management and also to assess the production potential of ELS genotypes compared with hirsutum hybrids. Amongst genotypes, seed cotton yield (kg/ha) was significantly higher with RCH659 BG II (H × H) (2839 kg/ha) The quality parameters results revealed that suvin non Bt showed the significantly highest fibre length (39.3 mm of 2.5% span length) and fibre strength (32.0 g/tex). Fibre quality was superior in early formed bottom bolls compared to middle and top bolls. Quality traits were highly correlated with duration of the crop as duration gets shorter, quality becomes deteriorated. The duration of the first squaring, 50% flowering, and 50% boll bursting were positively and significantly correlated with fibre length and strength . The duration of 50% squaring to first flowering was significantly positively correlated with uniformity ratio.The economic analysis showed that inter specific hybrid MRC 7918 BG II registered the highest net return (₹ 116916/ha) which is better than intra-hirsutum hybrid RCH659 BG II (H×H)( ₹ 99332/ha).